2001
DOI: 10.1097/00000542-200108000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Epidural Blood Patch in the Management of Post–Dural Puncture Headache

Abstract: Epidural blood patch is an effective treatment of severe post-dural puncture headache. Its effectiveness is decreased if dura mater puncture is caused by a large bore needle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
116
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(131 citation statements)
references
References 10 publications
6
116
0
7
Order By: Relevance
“…17 It should be noted that the authors of this study took great care in the interpretation of their results, noting that their findings may simply reflect the more refractory nature of more severe headaches, which are more likely to be associated with larger gauge needles, more likely to be treated earlier and probably more likely to fail therapy, rather than evidence to suggest that one should delay EBP to improve the odds of success following large gauge punctures. We believe that this carefully noted observation applies to the results found in our study and would not recommend delaying EBP in symptomatic patients following DP except in the cases where air headache is possible or alternative causes of PDPHlike symptoms are being entertained (for example, sagittal sinus thrombosis in pre-eclampsia).…”
Section: Discussionmentioning
confidence: 83%
“…17 It should be noted that the authors of this study took great care in the interpretation of their results, noting that their findings may simply reflect the more refractory nature of more severe headaches, which are more likely to be associated with larger gauge needles, more likely to be treated earlier and probably more likely to fail therapy, rather than evidence to suggest that one should delay EBP to improve the odds of success following large gauge punctures. We believe that this carefully noted observation applies to the results found in our study and would not recommend delaying EBP in symptomatic patients following DP except in the cases where air headache is possible or alternative causes of PDPHlike symptoms are being entertained (for example, sagittal sinus thrombosis in pre-eclampsia).…”
Section: Discussionmentioning
confidence: 83%
“…It is possible that these patients did not get enough information concerning treatment of headache or fear of the procedure kept them home. While drugs in treatment of PDPH are usually ineffective [19], epidural blood patching is safe, fast and effective in 90% of patients; and if repeated in patients showing a poor response the response rate rises up to 98% [20][21][22][23]. Despite that, epidural blood patch is underused in the treatment of patients with diagnostic lumbar puncture.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical experience has shown that epidural blood patch by preventing leakage through occluding the perforation is an effective therapy to treat a persistent post-spinal headache, with a success rate of more than 90% (3,4,5,34). However, as mentioned in the Introduction, a small CSF leakage is not compatible with a marked symptomatic influence on pain-sensitive regions of the brain, and especially not with the postural properties of the post-spinal headache, or the fact that the headache often disappears promptly after application of the blood patch.…”
Section: Discussionmentioning
confidence: 99%